Resonating valence bond quantum Monte Carlo: Application to the ozone molecule - Azadi, Sam; Singh, Ranber; Kühne, Thomas D. (International Journal of Quantum Chemistry, 2015)
We study the potential energy surface (PES) of the ozone molecule along the normal modes by means of Quantum Monte Carlo simulations based on the resonating valence bond concept. The trial wave function consists of an antisymmetrized geminal power arranged in a single determinant that is multiplied by a Jastrow correlation factor. Whereas the determinantal part incorporates static correlation effects, the augmented real-space correlation factor accounts for the dynamics electron correlation. The accuracy of this approach is demonstrated by computing the dissociation energy and PES for the ozone molecule in three vibrational states: symmetric, asymmetric, and scissoring. We find that the employed wave function provides a detailed description of rather strongly correlated multireference systems, which is in quantitative agreement with experiment, using a single determinant only.
CRIS-Team Scopus Importer:2023-03-20
Keywords: dynamics electron correlation; quantum Monte Carlo; resonating valence bond; static electron correlation